CSPα—chaperoning presynaptic proteins - Donnelier, Julien; Braun, Janice E. A. (Frontiers in Cellular Neuroscience, 2014)
Synaptic transmission relies critically on precisely regulated and exceedingly fast protein-protein interactions that involve voltage-gated channels, the exocytosis/endocytosis machinery as well as signaling pathways. Although we have gained an ever more detailed picture of synaptic architecture much remains to be learned about how synapses are maintained. Synaptic chaperones are ‘folding catalysts’ that preserve proteostasis by regulating protein conformation (and therefore protein function) and prevent unwanted protein-protein interactions. Failure to maintain synapses is an early hallmark of several degenerative diseases. Cysteine string protein (CSPα) is a presynaptic vesicle protein and molecular chaperone that has a central role in preventing synaptic loss and neurodegeneration. Over the past few years, a number of different ‘client proteins’ have been implicated as CSPα substrates including voltage-dependent ion channels, signaling proteins and proteins critical to the synaptic vesicle cycle. Here we review the ion channels and synaptic protein complexes under the influence of CSPα and discuss gaps in our current knowledge.